Soft Skill Improvement as a Data Update Effort in the Mekarsaluyu Village Development Program - Utami -; Wahyu Buana Putra; Dian Duhita (Journal of Innovation and Community Engagement, 2021)
Natural wealth is an enormous gift. Located in northern part of Bandung, in a mountainous area, Mekarsaluyu Village has vast natural potential. The cool air, beautiful scenery, and the existence of rivers and contoured land, and the culture in the form of art and traditional music and culinary make the village has a unique local wealth. However, the local wealth available has not been managed well. The potential referred to has not yet had an optimal positive impact both on the social and economic life of its inhabitants. The background of this problem gives encouragement to empower the people of Mekarsaluyu Village by planning a tourist village development program with the theme of ecotourism. To design the program, it was necessary to collect data on the existing conditions in Mekarsaluyu Village, covering the physical aspects of natural resources and the non-physical aspects of the socio-cultural community. Getting real, accurate, and actual needs necessary to update the data and complete the lack of required data, were important for determining the ecotourism village program's planning. Therefore, the aim of this work was to carry out community service in counseling on updating data for Mekarsaluyu Village residents. The method used was in the form of training and assistance in filling out data. The writing team prepared the necessary database format tools in data variables related to the ecotourism village planning program. Then together with the residents, simulated the form filling. The results obtained from this community service are the ability of villager residents to fill in actual data independently with accuracy and validity related to physical data on the natural geographical conditions and Mekarsaluyu Village's socio-cultural community. Keywords: natural resource; training; updating data; village development